Hollow Men : Writing, Objects, and Public Image in Renaissance Italy. - Gaylard, Susan (Fordham University Press, 2013)
"Analyzes texts and art objects from the 15th to the late 16th centuries to show that Renaissance theories of emulating classical heroes generated a deep skepticism about representation, as these theories forced men to construct a public image that seemed fixed but could adapt to changing circumstances"--